Fonctions du Cliché : du Banal à la Violence - Claudine Raynaud, Peter Vernon (dir.) (Presses universitaires François-Rabelais, 1997)
The first meaning of the word ""cliché"" is ""positive"": in typography a cliché is a metal plate upon which an image is reproduced in relief. In photography, however, cliché is a ""negative"" and, indeed, its most current acceptation is that of commonplace, banality, cultural stereotype, repetition. It makes reproduction possible and authorizes it. Bearing the positive and negative poles in mind, together with the dynamic of their potential inversion, one arrives at the core of the concept of clic...